ECO-FRIENDLY MANAGEMENT OF POTATO CYST NEMATODES IN THE NILGIRIS OF TAMIL NADU - Umamaheswari, R; Somasekhar, N; Manorama, K; Joseph, T A (Potato Journal, 2013)
Potato cyst nematodes (PCN) viz., Globodera rostochiensis and G. pallida are one of the most destructive pests of quarantine significance hindering the potato production in the Nilgiris region of Tamil Nadu. Hence two different field experiments were conducted from 2007 to 2009 to study the effect of organic amendments and biocontrol agents on PCN multiplication and potato yield. Organic amendments viz., eucalyptus de-oiled leaves, spent mushroom compost and neem cake individually and in combination with Trichoderma viride and biocontrol agents viz., Paecilomyces lilacinus, Pochonia chlamydospora, Trichoderma viride, Pseudomonas fluorescens Pf1 strain and Pseudomonas sp. were evaluated. Among the organic amendments, neem cake in combination with T. viride recorded significantly higher plant growth parameters and tuber yield (18.44 t/ha ) and was on par with carbofuran (17.16 t/ha). However, the PCN population in soil and roots and PCN multiplication were significantly lower in carbofuran treatment and was on par with neem cake in combination with T. viride. Among the biocontrol agents, P. fluorescens Pf1 recorded significantly higher growth parameters and yield (16.03 t/ha) coupled with lower PCN population in soil and roots and nematode multiplication (Rf - 1.38). However, carbofuran treatment performed better than all the biocontrol agents tested (Rf - 0.88).